Action of adrenal and gonadal steroid hormones on kainic acid-evoked seizures in a rat model of epileptogenesis - Slavina Surcheva; Stanislav Marchev; Roman Tashev; Stilyana Belcheva; Mila Vlaskovska (Biotechnology & Biotechnological Equipment, 2017)
Epilepsy is one of most reported neurological disorders after migraine, stroke and Alzheimer's disease. Empiric clinical data reveal that seizures and epilepsy more likely affect men than women. The aim of present study was to investigate the effect of steroid adrenal and gonadal hormones on the intensity, dynamics and latency of kainic acid-evoked seizure and lethality in a rat model of epileptogenesis. After surgical adrenalectomy/gonadectomy, male rats were at random assorted in groups and treated from postoperative day 1 to day 5 with corticosterone (30 mg/kg), estradiol (0.03 mg/kg), progesterone (75 mg/kg), dihydroprogesterone (75 mg/kg) and dihydrotestosterone (0.75 mg/kg). Spontaneous recurrent seizures generated by kainic acid were assessed. The treatment with corticosterone eliminated the aggravation of kainic acid-evoked seizures produced by adrenalectomy/gonadectomy. The application of corticosterone decreased the seizure intensity by 31% and prevented seizure-associated animal death. The effect of estradiol treatment was quite opposite. Estradiol treatment exacerbated the somatic and behavioural aspects of kainic acid-evoked epilepsy-like syndrome. The hormone increased the intensity of kainic acid-evoked seizures by 31%, decreased the latency of clonic weak seizures by 49% and enhanced the associated lethality by 133%. The treatment with progesterone or dihydroprogesterone produced minor alterations in intensity and latency of kainic acid-evoked seizures in the operated male rats. The application of dihydrotestosterone significantly aggravated the kainic acid-evoked seizures. In summary, hormonal unbalance could play an important role for seizure susceptibility in epileptogenesis. Corticosterone has better anti-seizure activity than progesterone and testosterone has significant pro-convulsive activity.